ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011-2013 (Students' Journal of Accounting and Banking, 2015)
This study aimed to obtain empirical evidence whether the income goes, the size of the company, the amount of KAP and debt proportion lag effect on the audit report on manufacturing companies in Indonesia Stock Exchange Period 2011-2013. The population in this study are all companies listed in Indonesia Stock Exchange in the year 2011 to 2013 observations. The samples in this study using purposive sampling method of sample selection is not random that the information obtained by certain considerations. Data were analyzed using multiple linear regression analysis. The results showed that (1) Profit and loss runs not significantly affect the audit report lag on Manufacturing companies listed in Indonesia Stock Exchange in 2011-2013. (2) Variable sized companies negatively affect the audit report lag g. (3) The amount of KAP negative effect on the audit report lag. (4) Debt proportion has a significantly positive effect on the audit report lag Keywords: profit and loss runs, the size of the company, the size of the firm, debt proportion and the audit report lag